ANDROID BASED VEHICLE TRACKING SYSTEM - Bhargav, Abhinav (My University, 2016)
The current location and estimated arrival time and distance of the vehicle is provided to the passenger by the vehicle tracking system. In relation to the estimated arrival time the passengers can decide whether to wait for the vehicle or not. This helps in making better travelling decisions by the passengers. From this system it can also be determined whether the vehicle is yet to come or has been missed. To make life more efficient the system provides necessary basic information. Android based vehicle tracking system is required which tracks the real time location of the vehicle and this information is used effectively by the commuters to make better travelling decision. GPS is growing its popularity in day to day life applications. In this era of 4th Generation Smartphone and palmtops have become a valuable part of the human beings. We often listen to the words Android and Maps. Android has made life easier and comfortable This thesis describes the process of designing a client server android based application for the efficient vehicle tracking. Quality of life of people in India is demeaning with the growing traffic congestion. Congestion leads to air pollution, decrease in accessibility and increased travel time. System and technology is growing even in microseconds. GPS is mounting its reputation in day to day life applications. With increasing use of smart phones and growing popularity of the GPS based applications, it has become feasible for the commuter to track the real time position of the vehicle and make better travelling decision.
Keywords: Android; Vehicle Tracking System